2008
DOI: 10.1007/s10165-008-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glucocorticoid on bone in 3-, 6-, and 12-month-old rats as determined by bone mass and histomorphometry

Abstract: The influence of glucocorticoid (GC) on bone in rats at different ages was investigated in order to provide insight into human glucocorticoid induced osteoporosis (GCOP). Three-, 6-, and 12-month-old female Wistar rats were divided into four groups: Zero-time control (ZT), vehicle (Cont), prednisolone (PSL) 2 mg/kg (P-L), PSL 20 mg/kg (P-H). PSL was subcutaneously administered every day for 4 weeks. Bone mineral density (BMD) at the proximal metaphysis and diaphysis of the tibia was measured by peripheral quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…The decreased TRACP 5b level can indicate both decreased bone resorption due to a lower osteoclast number, and a lower number of osteoclasts due to the bone loss induced by prednisolone treatment. In conclusion, 4-week prednisolone administration caused inhibition of both bone formation and resorption, consistent with a previous study [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decreased TRACP 5b level can indicate both decreased bone resorption due to a lower osteoclast number, and a lower number of osteoclasts due to the bone loss induced by prednisolone treatment. In conclusion, 4-week prednisolone administration caused inhibition of both bone formation and resorption, consistent with a previous study [25].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study of Ogoshi et al [25] demonstrated that 6-monthold female rats treated with 20 mg/kg prednisolone sodium succinate (sc) for 4 weeks were suitable models for glucocorticoid-induced osteoporosis, with a dominant cancellous bone decrease and reduced bone turnover, both formation and resorption. Our observations from the current study on male rats of a similar age (24 weeks) given prednisolone 21-hemisuccinate sodium salt at a dose of 7 mg/kg daily for 4 weeks are consistent with their results.…”
Section: Discussionmentioning
confidence: 99%
“…CCs also have been reported to increase bone resorption, particularly during the early phase of treatment, by stimulating osteoclastic activity and survival through an effect on the RANKL/OPG signaling pathway 21–23. Consistent with these findings, studies in animals24 and in humans25–33 have shown that administration of GCs significantly reduce biochemical markers of bone formation but have no effect or even increase those of bone resorption. Remarkably, administration of prednisone to our patient decreased not only bone formation but also bone resorption within 4 weeks of starting of treatment.…”
Section: Discussionmentioning
confidence: 78%
“…Reductions in bone mineral density occur due to deficient calcium intake or corticosteroids both in humans and animals (Lill et al 2002). However, the reports remain contradictory, attributable to the fact that experimental glucocorticoid administration shows either increased BMD or decreased BMD in rats (Ogoshi et al 2008). However, the reports remain contradictory, attributable to the fact that experimental glucocorticoid administration shows either increased BMD or decreased BMD in rats (Ogoshi et al 2008).…”
Section: Discussionmentioning
confidence: 99%